(untitled) (Journal of Economic Research & Business Administration, 2016)
There are a lot of projects and strategies are accepted tp develop Kazakhstan’s innovative activity, innovative infrastructure is carried out. A lot of expeditions are taking place, articles are written and developed. But this questions cannot be solved yet, because it hard to bind business eith science. The word science frightens and mistrusts businessman, young people doesn’t have will to do science. One way to atract young people to science is to build innovative activity of technopark structure and to involve students and magistrants to its managing process, to supply them with workplace connected with it and to improve the science status. The main aim of innovative process is to improve economic, sciencetechnic, ecological and social state of the country by entering innovation, therefore it will inprove the competetiveness of the country. Nowadays Kazakhstan’s economic state has big opportunity to carry out technological innovations,for example to make tools that are neccessary to produce machine and to do the mining and agricultural production, to find and unite new methods to save the agricultural production.